How To Cheat At Installing, Configuring And Troubleshooting Active Directory And Dns - Craft, Melissa (Syngress Publishing, Inc., 2011)
This special Syngress e-book is designed to provide quick, step-by-step help to anybody trying to wrestle with Win 2K Active Directory and DNS configuration